2021
DOI: 10.1016/j.tranon.2021.101208
|View full text |Cite
|
Sign up to set email alerts
|

FGF9/FGFR1 promotes cell proliferation, epithelial-mesenchymal transition, M2 macrophage infiltration and liver metastasis of lung cancer

Abstract: Highlights FGF9 induced cell proliferation, EMT, migration, and invasion of mouse Lewis lung cancer (LLC) cells, in vitro . FGF9 interacted with FGFR1 and activated FAK, AKT, and ERK/MAPK signal pathways, induced the expression of EMT key proteins (N-cadherin, vimentin, snail, MMP2, MMP3 and MMP13) and reduced the expression of E-cadherin. FGF9 promoted liver metastasis of subcutaneous inoculated LLC tumor with tumor grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 75 publications
0
21
0
Order By: Relevance
“…Analysis results of immune-related genes in HCC showed that NR0B1 and FGF9 were risk factors for HCC, and experiments confirmed that NR0B1 and FGF9 could enhance the migration ability of macrophages. The study by Chang et al confirmed that FGF9 can enhance the immune infiltration ability of M2 macrophages [ 31 ]. KEGG enrichment analysis demonstrated that IRGs were mainly enriched in immune-related pathways such as chemokine signaling pathway, which can confirm that the prognostic model constructed according to immune-related genes of HCC in this study has high reliability.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis results of immune-related genes in HCC showed that NR0B1 and FGF9 were risk factors for HCC, and experiments confirmed that NR0B1 and FGF9 could enhance the migration ability of macrophages. The study by Chang et al confirmed that FGF9 can enhance the immune infiltration ability of M2 macrophages [ 31 ]. KEGG enrichment analysis demonstrated that IRGs were mainly enriched in immune-related pathways such as chemokine signaling pathway, which can confirm that the prognostic model constructed according to immune-related genes of HCC in this study has high reliability.…”
Section: Discussionmentioning
confidence: 99%
“…The supernatants were then harvested and stored at -80 ˚C until further use. The protein concentration of the cell lysates was determined using a Micro BCA assay (44,45). For western blot analysis, ~30 µg lysates per lane were resolved on a 12% SDS-PAGE gel with standard running buffer (24 mM Tris/HCl, 0.19 M glycine, 0.5% SDS, pH 8.3) at 25˚C, and were subsequently transferred to PVDF membranes at 4˚C.…”
Section: Methodsmentioning
confidence: 99%
“…73 FGFRs are involved in various biological processes such as cell proliferation, migration and EndMT. 74,75 FGFR1, a key anti-EndMT molecule, is an endothelial receptor required for counteracting EndMT. 76 Chen et al 77 reported that endothelial FGFR1 deficiency was associated with increased TGFβ signalling and Smad2 activation, which exacerbates EndMT through enhanced TGFβ signalling.…”
Section: Fgfr1 Signalling Pathwaymentioning
confidence: 99%